The Mahdi's Legal Methodology as a Mechanism for Adapting the Sharî'a in the Sudan to Political and Social Purposes - Aharon Layish (Revue des Mondes Musulmans et de la Méditerranée)
Muhammad Ahmad b. 'Abd Allâh (best known as Muhammad al-Mahdî) headed a religious-political movement for the revival and reform of Islam (Mah-diyya) in the late 19th century. The success of the Mahdi's endeavour to consolidate a radical theocracy in a society well-entrenched in tribal customary law was dependent on the transformation of orthodox shan'a to the extent that was necessary to meet custom half-way and to enable a charismatic leader enough room to manœuvre to solve daily political and social problems arising within a theocracy.For this purpose, the Mahdi created a unique legal methodology that provided him with unlimited authority to enact legal rules without any institutional restriction on the part of the orthodox 'ulamâ'. He abolished all schools of law (madhâhib) and acknowledged three sources of law : the Prophetic sunna, the Quran and inspiration (ilhâm) transmitted to him by the prophet Muhammad. The Mahdi's version of ijtihâd is not compatible with classical theory.The application of his legal methodology enabled the Mahdi to introduce innovations, some of which were far-reaching deviations from orthodox sharî'a. This essay analyses some of these innovations in various domains of Islamic law arranged according to goals promoted by the Mahdi. It is based on a small sample out of more than 1,000 legal documents issued by the Mahdi from the time of his manifestation in 1881 until his death in 1885.